(untitled) (Fiep Bulletin - online, 2015)
Cases of burns are not uncommon in routine health services. The effects generated by injuries require careful treatment and ongoing interventions in the rehabilitation process of patients. In this sense, the pain caused by the procedure ends also mobilizing the team that provides care to these patients. The objective of this work is to understand the experience of care with patients with burns from the perspective of staff and possible interventions psychologist these professionals. The method consists of qualitative research based on analysis of participant observation and fieldwork diary produced during extracurricular internship at the Burns Unit of a public hospital, located in the state capital of Rio Grande do Sul. The results show that besides the importance of psychologist interventions alongside patients and families realize the importance of monitoring difficulties faced by staff in patient care with burns. Perform procedures that involve the treatment of burns and deal with the pain of others, also hurts. Feel hurt by another health condition, it is the pain itself, which refers to our existence as a subject and also to our death. In this sense, it is important to enable a space for listening also to the professionals, so that they can speak of their suffering, their pain, since they refer to their existence and subjectivity.